Analisis Tingkat Kognitif Pada Soal LKS SMP Kelas 8 Berdasarkan Taksonomi Bloom Revisi - Fitriani, Melia Sari; Susanta, Agus; Agustinsa, Ringki; Utari, Tria (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2021)
This study aims to determine the cognitive level of the questions on the LKS SMP grade 8 based on the revised bloom taxonomy. This type of research is descriptive with a qualitative approach. The type of research used is descriptive with a qualitative approach. Sources of data in this study are the total number of questions on the flat-sided shape of the math worksheets for class 8 semester 2 on the material of flat-sided shapes. The results of this study show that of 42 questions C1 (Remember) of 9,524% with a cognitive process of